Pattern of Childhood Thyroid Malignancy Referred to INMAS, Dhaka, for Radioiodine Ablation in A Decade (Bangladesh Journal of Nuclear Medicine, 2025)
Objectives: Thyroid cancer is the third most common cancer in children. It represents 1% to 1.5% of all pediatric cancers. Papillary thyroid cancer is common thyroid malignancy in children. This study is designed to see the pattern of thyroid malignancy in children in our institute. Patients and Methods: This retrospective study was carried out in INMAS, Dhaka, from January 2005 to December 2014. Data from case files of thyroid cancer patients of pediatric age group were recorded. Results: Total 40 pediatric patients, 35 females and 5 males (F: M: 7:1, age range-9-18 years, mean age-13±1years) in this study came after total thyroidectomy for thyroid malignancy. Among them 24 patients (F-21, M-3,60%) had papillary thyroid carcinoma (PCT), 3 patients (F-2 M-1, 7.5%) had follicular thyroid carcinoma (FCT), 12 patients (F-11, M-1,30%) had PCT with lymph node metastasis, and one patient had medullary thyroid carcinoma. One patient had PCT with hashimoto’s thyroiditis, another had PCT with pulmonary tuberculosis and one had FCT with diabetes with hyperparathyroidism. Radioiodine ablation therapy was given to all patients according to staging and grading of tumor. Conclusion: The prognosis for thyroid carcinoma in children is excellent. Proper treatment and regular follow up are needed for this disease.Bangladesh J. Nuclear Med. 27(2): 180-184, 2024